Efficacy of Olfactory and Pareidolia Tests Compared With That of Indicative Biomarkers in Diagnosis of Dementia With Lewy Bodies - Inagawa, Yuta; Kanetaka, Hidekazu; Tsugawa, Akito; Sakurai, Shu; Serisawa, Shuntaro; Shimizu, Soichiro; Sakurai, Hirofumi; Hanyu, Haruo (Frontiers in Neurology, 2020)
Purpose: Although olfactory decline and visual hallucinations are useful in distinguishing dementia with Lewy bodies (DLB) from Alzheimer's disease (AD) in a clinical setting, neither is easy to evaluate objectively. The pareidolia test is used to assess susceptibility to visual hallucinations, while in Japan, the Odor Stick Identification Test for the Japanese (OSIT-J) is used to objectively quantify olfactory decline. The present study investigated the efficacy of these olfactory and pareidolia tests in differentiating AD from DLB. Their usefulness was then compared with that of the indicative biomarkers in neuroimaging for a clinical diagnosis of DLB listed in the Fourth Consensus Report of the Dementia with Lewy Bodies Consortium. Methods: A total of 24 probable DLB and 22 probable AD patients were enrolled. All underwent 4 diagnostic procedures: uptake of dopamine transporter in single photon emission computed tomography (DaT-SPECT) and meta-iodobenzylguanidine (MIBG) in myocardial scintigraphy, the pareidolia test, and OSIT-J. The sensitivity, specificity, and accuracy of these methods in differentiating DLB from AD were compared. Results: Sensitivity and specificity in differentiating DLB from AD were 86 and 100% by the heart-to-mediastinum ratio of MIBG uptake; 82 and 96% by the specific binding ratio on DaT-SPECT; 77 and 67% by the combination of OSIT-J and pareidolia test scores; 73 and 62% by the pareidolia test scores; and 77 and 58% by the OSIT-J scores, respectively. Conclusions: The present results suggest that the pareidolia and OSIT-J tests may be considered before resorting to nuclear neuroimaging in the diagnosis of DLB.